ISOLATION AND CHARACTERIZATION OF UNIQUE FRUCTOPHILIC LACTIC ACID BACTERIA FROM DIFFERENT FLOWER SOURCES. - M. Saleh, G. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate Lactic acid bacteria (LAB) that contain an important group of bacterial strains such as fructophilic lactic acid bacteria that usually isolated from fructose rich niches. These groups of bacteria have been considered as probiotics, especially in animal applications. In this study these bacteria were isolated from 6 Plant sources (flowers) such as: Convolvulus arvensis, Hibiscus rosa-sinensis , Nerium oleander, Rosa rugosa, Tagetes erecta and Zinnia elegans. The bacterial isolates were identified by morphological and molecular methods through the detection of 16SrRNA gene. Carbohydrate fermentation profile as well as their antibacterial activity using the dual culture overlay assay was also detected. The results revealed that 5 types of different lactic acid bacteria were isolated included: Fructobacillus fructosus, Lactobacillus kunkeei, Enterococcus durans, Enterococcus faecium , and Lactobacillus brevis. These isolates showed variety in fermentation of carbohydrates. Also, all isolates exhibit inhibition effect against pathogenic bacteria (Staphylococcus auresو Pseudomonas aeruginosa) except Enterococcus faecium which showed no effect it.